Particle size dynamics and risk implication of atmospheric aerosols in South-Asian subcontinent. (June 2020) - Rohra, Himanshi; Pipal, Atar S.; Tiwari, Rahul; Vats, Pawan; Masih, Jamson; Khare, Puja; Taneja, Ajay
Abstract: Presented here are size-resolved aerosol measurements conducted using cascade impactor set at breathing zone in indoor-outdoor residential microenvironments. PM2.5 contributed about 64–80% of PM10 in which over 29% of mass was shared by PM0.25. Total PM concentration varied from 261 ± 22 μg/m 3 ( indoors ) to 256 ± 64 μg/m 3 ( outdoors ) annually; whilst summer and monsoon demonstrated 1.2- and 1.9- times lower concentration than winters. The measured metals ranged between 9% (in PM2.5-10 ) to 18% (in PM1-2.5 ) of aerosol concentration; whereby crustal elements dominated coarse fractions with relatively higher proportion of toxic elements (Ba, Cd, Co, Cr, Cu, Ni) in ultrafine range. Considering lognormal particle size distribution (PSD), accumulation mode represented the main surface area during entire monitoring period (Mass Median Aerodynamic Diameter (MMAD) < 1). PSD of metal species reflected their different emission sources with respect to season integrated samples. High air exchange conditions permitted the shift of indoor PSD pattern closer to that of outdoor air while low ventilation in winters reflected modal shift of metals (Pb, Mg. K) towards larger size particles. Relative surge towards smaller diameter size of soluble metal fraction relative to the total concentration of toxic elements was noted on an annual basis with high infiltration capacity of smaller size particulates ( Finf =1.36 for ultrafine particles in summers) identified through indoor-outdoor regression analysis. Principal Component Analysis identified sources such as vehicular traffic, combustion, crustal emission with activities viz. smoking and those involving use of electric appliances. Graphical abstract: Image 1 Highlights: Evidence suggestive of differential metal toxicity and sources (vehicular, combustion etc.) in residences are discussed. Breakdown of PM2.5 mass revealed higher occupancy (>30%) of q-UFP range. Increased correlation (R 2 > 0.5) for elements in ultrafine and accumulation range. The mass peak of metals (Pb, Mg, K) shifted to larger sized particles from high to low ventilation conditions. PM and bounded metals depicted seasonal variability in their size distribution pattern.